BREAST HAMARTOMA: 21 CASES - Ali İbrahim Sevinç; Merih Güray; Pınar Balcı; Mehmet Ali Koçdor; Serdar Saydam; Ömer Harmancıoğlu (European Journal of Breast Health, 2009)

(untitled)
Introduction: Breast hamartoma is a benign lesion, composed of varying amounts of fatty, fi brous and glandular elements. Clinical presantation is that of a well-circumscribed mass of soft-to-fi rm consistency feels similar to normal breast tissue. It is a rare clinicopathologic entity.Material and methods: The medical records of 21 patients with a diagnosis of breast hamartoma at our clinic between 1996-2009 were retrieved.Results: All the patients were female and the mean age was 47 (27-56). All of the patients visited to our clinic with a palpable mass on their breast. Mammography and ultrasonography was performed to all of them. All of the cases were underwent excisional biopsy.Conclusion: The incidence of mammary hamartoma is 0.7- 0.1 % of all benign mammary tumors. They are probably more common than anticipated in the literature. The lack of spesifi c histological features is responsible for the underestimation of its defi nition rate. However diagnosis is not diff ucult when it is made on the basis of a combination of clinical, radiologic and pathologic features. Mammary hamartoma is not a premalignant lesion. As it contains all the constituents of the normal breast tissue, a carcinoma can rarely be arising from these lesions. For that reason , excisional biopsy must be performed in the treatment of hamartomas to understand of its histopathologic entity.